2013
DOI: 10.1002/jgra.50394
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary compressible Kelvin‐Helmholtz surface wave instabilities on the Earth's magnetopause

Abstract: Primary and secondary Kelvin‐Helmholtz surface wave modes on the Earth's magnetopause are studied within the framework of warm plasma ideal magnetohydrodynamics (MHD) across an infinitely thin magnetopause tangential discontinuity (TD). With the increase of background flow velocity, a Kelvin‐Helmholtz Instability (KHI) unstable boundary separating two uniform semi‐infinite plasma regions is always ultimately stabilized to KHI growth at an upper cut‐off while inclusion of an inner boundary in one plasma region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
6
23
0
2
Order By: Relevance
“…Figure shows that the phase speed values of the KHI waves are in the expected range of fast MHD waves. This is consistent with the results of Turkakin et al [], where it is shown that the fastest growing KHI modes, i.e., primary KHI modes, are fast MHD waves.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure shows that the phase speed values of the KHI waves are in the expected range of fast MHD waves. This is consistent with the results of Turkakin et al [], where it is shown that the fastest growing KHI modes, i.e., primary KHI modes, are fast MHD waves.…”
Section: Resultssupporting
confidence: 93%
“…Some studies have assumed a zero thickness boundary, which is appropriate if the wavelengths of the generated waves are significantly larger than the thickness of the boundary [ Pu and Kivelson , ; Mann et al , ; Turkakin et al , , ]. The effects of a finite boundary thickness have also been investigated in several studies [ Ong and Roderick , ; Walker , ; Farrugia et al , ; Contin et al , ; Gratton et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…We also calculated the phase velocities, boldUp=ωr(kx2+ky2)boldk, periods, T r =2π/ ω r , and the propagation angles with respect the background flow, β = tan − 1( k y / k x ) for these modes. Normalized phase velocities show that the primary kink and sausage modes are fast waves, while the secondary kink and sausage modes are slow waves in the stationary plasma frame in region 1 (not shown here) consistent with the results shown in Turkakin et al []. Variations of propagation angles, β , with background flow are displayed in Figure c and are found to vary between ≃0°–64°for primary and ≃0°–40°for secondary KHI waves.…”
Section: Resultssupporting
confidence: 88%
“…The eigenfrequency variation with increasing normalized flow speed, V 02 = U 02 / V A 2 , in the channel is shown in Figures a and b, where both kink and sausage modes show two distinct K‐H unstable regions representing primary and secondary KHIs [c.f., Turkakin et al , ]. The secondary KHI becomes unstable at lower BBF flows, V 02 ≃2.8, than primary KHI, V 02 ≃3.3, which agrees with the results in Turkakin et al [].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation